The Relationship Between Bullying Victimization and Suicidal Ideation in Student Victims of Bullying in Yogyakarta - Debby Sannya Indah Putry M; Ratna Yunita Setiyani Subardjo (Publikasi Indonesia, 2024)
Suicidal ideation arises in individuals or groups who feel overwhelmed by pressure and a sense of hopelessness. Bullying is a significant factor that contributes to severe psychological and social impacts on both victims and perpetrators. The growing prevalence of bullying today requires special attention, as it not only harms the victims but also negatively affects the bullies themselves. This study uses the scale of the Relationship of Bullying Victimization to Suicidal Ideation (suicidal ideation) in students who are victims of bullying in Yogyakarta. The type of research used is correlational quantitative research. Quantitative research is a research method that aims to find out if the individual has experienced a victim of bullying that causes suicidal thoughts. Suicidal Ideation and Bullying are known to have a significance value of 0.736, where this value is greater than 0.05. So, it can be concluded that the two variables have a significant relationship or correlation with a strong correlation level. Victims of bullying can be open and seek help from their parents, close friends and family so that they do not experience the risk of suicidal ideation (suicidal ideation) or other effects of bullying. In addition, victims must have positive thoughts when they feel hurt so that they do not think badly to do suicidal ideation (suicidal ideation).